Description and access to the digitized photograph collection of the Ateneo de Manila University archives - Banal, Kareen J. (School of Library and Information Studies, University of the Philippines Diliman, 2018)
Aside from textual records, photographs also form a principal part of the collections that an archive safeguards. While preservation is one of the main endeavors and function of archiving, the utilization, promotion and access of this special material are equally important advocacy for an archive to look at while maintaining preservation responsibilities. Repeated handling and exposure of photographic prints may cause serious deterioration to this special collection and one of the go-to preventive measures is to digitize the collection. The University Archives of the Ateneo de Manila University adapted this method but, still, photographs relatively remained "hidden". With an aim to increase the discoverability of the photograph collection, this project is proposed aiming to describe and provide access to the digitized photos and deploy a system to augment the servicing of the collection.